Novel serum biomarker associations with 7 Tesla MRI-defined cortical lesions, leptomeningeal enhancement, and deep gray matter volume in early multiple sclerosis - Miclea, Andrei; Zurawski, Jonathan; Healy, Brian C.; Saxena, Shrishti; Lokhande, Hrishikesh; Quattrucci, Molly; Chu, Renxin; Weiner, Howard L.; Bakshi, Rohit; Chitnis, Tanuja (Scientific reports, 2025)
Gray matter demyelinating lesions, brain atrophy and meningeal inflammation are hypothesized to be relevant in multiple sclerosis (MS) disease pathogenesis, though their relationship to immune alterations in early MS is not well characterized. This study aims to investigate correlations between the concentrations of 112 serum proteins and 7 Tesla MRI-defined measures of disease severity in patients with early MS. In this analysis, patients with CIS or MS having a 7 Tesla brain MRI and blood sample both within five years of MS diagnosis were included (n = 57). Correlational analysis was adjusted for sex, age, and disease duration. Correlation between serum proteins and MRI-defined cortical and thalamic gray matter lesions, leptomeningeal enhancement (presence and foci number), deep gray matter (DGM) structure volumes, whole brain parenchymal volume and total T2 white matter lesion volume was assessed. In this study, cortical lesions were associated with higher IL-15, TNF-alpha, and BAFF levels, and lower levels of FcRL2. Leptomeningeal enhancement was associated with higher levels of PLXNB3 and lower levels of nCDase and CNTN5. Higher IL-1B levels correlated with lower DGM volume while higher levels of CDH6, SIGLEC9, and HAGH correlated with higher DGM volume. These novel associations between serum immune proteins and 7 T MRI outcomes may have relevance as disease biomarkers in early stages of MS.